Spatial stimulus configuration and attentional selection: extrastriate and superior parietal interactions. - Gillebert, C; Caspari, N; Wagemans, J; Peeters, R; Dupont, P; Vandenberghe, R (2013)
The intraparietal sulcus (IPS) is critical for resolving stimulus competition. Its activity is modulated depending on how competing stimuli are spatially configured. Lesions extending into IPS lead to selection deficits when stimuli are configured along a horizontal relative to a vertical or diagonal axis. Using functional magnetic resonance imaging, we examined whether the effect of configuration axis originates at the level of the sensory map in early visual cortex or at the level of the attentional priority map in IPS. In each trial, we presented 1 or 2 peripheral gratings in the upper right visual field and a central letter stream. Subjects performed either a peripheral orientation discrimination task or a central letter detection task. Left IPS activity was higher when peripheral stimuli were configured along the horizontal relative to the vertical axis, but only in peripheral attention conditions. The portions of extrastriate cortex that responded to the peripheral stimuli showed a similar interaction. Connectivity from superior parietal to extrastriate cortex was enhanced by adding a competing distracter during the peripheral attention task. The effect of the spatial configuration between competing stimuli originates at the level of the attentional priority map in IPS rather than the visual sensory map.